Exploration of Religious Moderation with Local Culture; A Case Study of the Samin Community of Bojonegoro - Setiawan, Nanang; Khamid, Abdul; Huda, Muhammad Miftakhul (Proceedings of Annual Conference for Muslim Scholars, 2023)
This research aims to explore how religious moderation is realized in the daily lives of the Samin Community of Bojonegoro. This research is qualitative, involving observations of the traditional life of the Samin community and in-depth interviews with local community leaders. The results of the research show several local wisdoms in the Samin Bojonegoro community: ngelmu iku sejatine dhewe, ngudi ilmu, ponco soco, ngluruk tanpa rupo, nyawiji sepi ing pamrih, nyawiji ngluruk, ngganem sepi ing ngluruk, and ngalembono. The results of the analysis reveal that local culture plays an important role in forming and maintaining religious moderation among the Samin Bojonegoro community. Customs and traditions are a strong foundation for tolerance between religious communities, thereby creating harmony amidst the diversity of beliefs. This study contributes to a deeper understanding of the balance between religious moderation and local culture, thereby providing new insights for researchers, practitioners, and readers interested in this field. It is hoped that this study will make a positive contribution to supporting a better understanding of religious moderation in the local context, with a special focus on the unique experiences of the Samin community.